Impact of pulmonary rehabilitation programme design on effectiveness in COPD: a systematic review and component network meta-analysisResearch in context - Thomas J.C. Ward; Lorna Latimer; Enya Daynes; Suzanne C. Freeman; Sarah Ward; Jiaqing Xu; Muhammed Haris; Majda Bakali; Sophie Reap; Mamoon Iqbal; Lin Wang; Akash Mavilakandy; et al. (EClinicalMedicine)
Summary: Background: Pulmonary rehabilitation (PR) is a key treatment for chronic obstructive pulmonary disease (COPD) recommended by all guidelines. However, programmes vary widely and the optimal combination of components to maximise benefits and efficiency remains unknown. We aimed to use the novel technique of component network meta-analysis (cNMA) to investigate the relative contribution of 1) exercise modality and intensity, 2) non-exercise components, 3) type of supervision, and 4) programme duration of PR for people with COPD. Methods: MEDLINE, EMBASE, CINAHL, and Cochrane databases searched in October 2023 with no date or language restrictions. We included randomised controlled trials (RCTs) which included an intervention involving exercise for people with COPD. We present outcomes of exercise capacity, breathlessness and health related quality of life (HRQoL). Screening and eligibility were assessed by two independent reviewers. cNMA, a technique developed to investigate complex interventions such as PR, was conducted to examine the contribution of single components within diverse multicomponent interventions controlling for cohort demographics. PROSPERO: CRD42022322058. Findings: We included 337 RCTs with 18,911 participants and 227 intervention components. In-person supervision enhanced gains in exercise capacity (Standardised mean difference (SMD) 0.41, 95% CrI 0.20; 0.63), HRQoL (0.43 95% CrI 0.19; 0.68) and breathlessness (0.31 95% CrI 0.04; 0.58) over exercise training alone with moderate to high certainty. Remote supervision increased gains in exercise capacity (0.40 95% CrI 0.08; 0.73) with trends towards improvements in HRQoL and breathlessness, with low certainty. Aerobic training appeared to be most effective for all outcomes at high or very high intensity but with low certainty. Addition of structured education did not improve any outcome. Psychological interventions led improvements in exercise capacity (0.37 95% CrI 0.01; 0.73, low certainty) and HRQoL (0.54 95% CrI 0.18; 0.91, moderate certainty). There was trend towards improvements in breathlessness with addition of breathing exercises (0.26 95% CrI −0.04; 0.56, low certainty). Programme duration did not impact outcomes. For outcomes of exercise capacity, HRQoL and breathlessness there were 60%, 63% and 59% studies at high risk of bias respectively. Interpretation: This large-scale analysis of over 300 randomised PR trials found the strongest effects for in-person supervised and prescribed aerobic exercise training with less certainty for the benefit of other commonly used PR components and delivery methods. Funding: This research was funded through a National Institute for Health and Care Research (NIHR) Applied Research Collaboration East Midlands grant (2.12) and carried out at the NIHR Leicester Biomedical Research Centre (BRC).